CANDIDEMIA IN PATIENTS WITH ACUTE LEUKEMIA: ANALYSIS OF SEVEN YEARS’ EXPERIENCE AT A SINGLE CENTER IN - Xiaoyuan Gong; mianzeng yang; Dong Lin; Hui Wei; Ying Wang; Bingchen Liu; Chunlin Zhou; Kaiqi Liu; Shuning Wei; Benfa Gong; Guancji Zhang; Yuntao Liu; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
The study of candidemia in Chinese leukemia patients has been limited. This retrospective study aims to investigate the characteristics and prognostic factors of candidemia among leukemia patients in a Chinese chemotherapy center.